The Complete Plastid Genome Sequence of the Wild Rice Zizania latifolia and Comparative Chloroplast Genomics of the Rice Tribe Oryzeae, Poaceae - Zhang, Dan; Li, Kui; Gao, Ju; Liu, Yuan; Gao, Li-Zhi (Frontiers in Ecology and Evolution, 2016)
Zizania latifolia (Griseb.) Turcz. ex Stapf was once utilized as an important grain in ancient China and has been cultivated as an aquatic vegetable. Here, we report the complete Z. latifolia chloroplast genome sequence obtained through de novo assembly of Illumina paired-end reads generated by directly purified chloroplast (cp) DNA genome sequencing. The Z. latifolia cp genome is 136,501 bp in length, comprising a pair of 20,878-bp inverted repeat regions (IR) separated by small and large single copy regions (SSC and LSC) of 12,590 bp and 82,155 bp, respectively. The Z. latifolia cp genome encodes 110 unique genes (77 protein-coding genes, 29 tRNA genes, and 4 rRNA genes), of which 15 encompass introns. Sequence analysis identified a total of 39 direct/inverted repeats and 63 simple sequence repeats (SSR) with an average rate of 0.46 SSRs/kb. Our results revealed that the Z. latifolia cp genome is AT-rich (61.02%) and gene codon usage may be largely affected by a low GC content and codon usage bias for A, T-ending codons. We predicted 33 RNA editing sites in the chloroplast of Z. latifolia, all for C-to-U transitions. Comparative analyses with other available Oryzeae plastid genomes showed that the coding and IR sequences were more conserved than the single-copy and noncoding regions, suggesting that the indels should be cautiously employed in phylogenetic studies. Phylogenetic analysis of 52 complete grass chloroplast genomes including the reported Z. latifolia cp genome in this study yielded an identical tree topology as previous plastid-based trees, providing strong support for a sister relationship between Bambusoideae+Pooideae and Ehrhartoideae in the BEP (Bambusoideae, Ehrhartoideae, Pooideae) clade of the grass family.